Pengaruh Harga, Pelayanan Dan Variasi Jasa Terhadap Kepuasan Konsumen Dalam Menggunakan Transportasi Online (Studi Kasus Pada Pelanggan Go-Jek Di Kota Yogyakarta) - Winanto Nawarcono (Solusi: Jurnal Kajian Ekonomi dan Bisnis, 2019)
The purpose of this study was to determine the effect of price, service and service variation on customer satisfaction in using GO-JEK online transportation services. Data was obtained by distributing questionnaires to consumers who had already used GO-JEK online transportation services. The method used in this study is multiple linear regression analysis, t test, F test and R2 (coefficient of determination). Based on multiple linear regression analysis, it can be concluded. Significance test influence partially obtained the results that the independent variables namely price, service and service variations have a significant effect on consumer satisfaction. This is evidenced from the calculation of the t test, the t value is greater than t table. Significance test of the influence together shows that there is a significant influence between price, service and service variation on customer satisfaction. This is evidenced from the calculation of the F test where F count is greater than F table which is equal to 33.192> 2.699. The coefficient of determination (R2) is 0.494. This value shows that the independent variables (price, service and service variation) can explain its effect on consumer satisfaction by 49.4%. While the rest is explained by other variables not included in this research model.